The statu quo of the Gulf of Fonseca. The conflictual potential of an unfinished project - Gutiérrez Castillo, Víctor Luis (REVISTA ELECTRONICA IBEROAMERICANA, 2023)
The Gulf of Fonseca is known as one of the few territories where there is an international condominium. The apparent success of this formula contrasts with the intermittent tensions between its states, with the consequent deterioration of neighborhood relations. The Republics of El Salvador, Nicaragua and Honduras are bound (asymmetrically) by the judgments of different international tribunals, issued in the framework of territorial disputes at different historical moments. Three decades after the last judgment of the  nternational Court of Justice, and far from there being a consensus in the region, there are still conflicting positions among the States of the Gulf of Fonseca regarding the interpretation and application of the court decisions. The aim of this paper is to analyse the current statu quo in the Gulf, as well as the reasons that explain the potential for conflict in the area.
Keywords: Condominium; Gulf of Fonseca; conflict; International Court of Justice; International Cooperation